Proposal for a Social Impact Bond for reduction of recidivism in the Czech Republic - Kubik, Adam (2020)
The diploma thesis aims to propose a Social Impact Bond (SIB) for reduction of recidivism in the Czech Republic. The theoretical part presents the key criteria for success and how to avoid mistakes that may occur with SIB. The empirical part is focused on the SIB setup itself. First of all, it is a definition of key determinants influencing repeat crime. The results show that young men without a university degree are most likely to commit another crime. This probability is further exacerbated by the number of previous crimes committed. The social program within the SIB should thus focus on individuals with these characteristics, especially in the first year after their release from prison. The estimated societal costs of recidivism reached almost CZK 25.5 billion in 2018, which, however, are still underestimated due to the large number of incalculable latent cases. Reducing recidivism by only 7.5% would thus bring social savings of almost CZK 2 billion, which can also serve as an amount for which the SIB can be issued. SIB's profitability is difficult to determine due to the great diversity of social program settings.